2009
DOI: 10.4038/sljch.v34i4.389
|View full text |Cite
|
Sign up to set email alerts
|

A survey on febrile seizures at the Lady Ridgeway Hospital for Children

Abstract: Objectives To evaluate demographic, clinical and management aspects of febrile convulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
2
1
Order By: Relevance
“…1 Also, the mean age of onset of seizures is consistent with previous studies reported. 3,45 This study also documented the recurrence rate of FS to be 25.4%, which was close to 30% documented in the literature. 11,24,27 Finally, poor knowledge of what to do by the parents when a child convulsed is also obvious in this study, which is also similar to the findings of Oche et al in Sokoto, Nigeria.…”
Section: Journal Of Pediatric Neurologysupporting
confidence: 86%
See 2 more Smart Citations
“…1 Also, the mean age of onset of seizures is consistent with previous studies reported. 3,45 This study also documented the recurrence rate of FS to be 25.4%, which was close to 30% documented in the literature. 11,24,27 Finally, poor knowledge of what to do by the parents when a child convulsed is also obvious in this study, which is also similar to the findings of Oche et al in Sokoto, Nigeria.…”
Section: Journal Of Pediatric Neurologysupporting
confidence: 86%
“…This is also consistent with report from documented research studies. 3,45,48 There was a family history of FS in 6.2% of the first degree relative, which is lower than what was reported in the previous study by Pathirage. 50 About half of the patients had their first seizure episodes under the age of 1 year and this is similar to a report of an earlier study done by Van der Berg and Yerushalmy.…”
Section: Journal Of Pediatric Neurologycontrasting
confidence: 56%
See 1 more Smart Citation
“…The study sample was calculated using the formula by Lwanga and Lameshow 12 based on the previous study done on children with FS at the same hospital 13 . Two study instruments were used.…”
Section: Methodsmentioning
confidence: 99%